Multipath Impact on Multi-Frequency and Multi-Constellation Code Measurements from Brazilian GNSS Stations - Setti, Paulo T.; da Silva, Crislaine Menezes [UNESP]; Alves, Daniele Barroca Marra [UNESP]; Vieira, João Vitor Espinhosa [UNESP]; Zaupa, João Pedro Voltare [UNESP] (Universidade Federal do Rio de Janeiro, 2023)
Although Global Navigation Satellite Systems (GNSS) positioning can achieve high accuracy in line-of-sight conditions, multipath remains a dominant source of error. Multipath occurs when the reflected signals reach the receiver in addition to the direct ones. Different systems design can impact the multipath effect, such as the signal modulation and chipping rate. In the context of multi-frequency and multi-constellation scenario that we are achieving with four operational global constellations, this paper compares the multipath impact in different signals of GPS, GLONASS, Galileo and BeiDou. For the experiment, one week of data from 35 Brazilian Network for Continuous Monitoring of the GNSS Systems (RBMC) stations in June 2021 was processed. The multipath index was estimated based on the code-minus-carrier combination. For the first frequency of each system, similar results were obtained for GPS, GLONASS and BeiDou (approximately 56 cm). The Galileo BOC/AltBOC modulation offers better resistance to multipath, with a multipath index of 37 cm for E1 and of 12 cm for E5. Considering all selected stations, the multipath index of GPS L1 varied from 38 cm to 61 cm.
Impacto do Multicaminho em Observações Multifrequência e Multi-Constelações de Pseudodistância em Estações GNSS Brasileiras
Keywords: Galileo; GLONASS; RBMC